2018
DOI: 10.3389/fimmu.2018.01125
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Programmed Death-Ligand 1 by Human Colonic CD90+ Stromal Cells Differs Between Ulcerative Colitis and Crohn’s Disease and Determines Their Capacity to Suppress Th1 Cells

Abstract: Background and AimsThe role of programmed cell death protein 1 (PD-1) and its ligands in the dysregulation of T helper immune responses observed in the inflammatory bowel disease (IBD) is unclear. Recently, a novel concept emerged that CD90+ colonic (myo)fibroblasts (CMFs), also known as stromal cells, act as immunosuppressors, and are among the key regulators of acute and chronic inflammation. The objective of this study was to determine if the level of the PD-1 ligands is changed in the IBD inflamed colonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 59 publications
4
43
0
Order By: Relevance
“…22 PD-L2 is generally expressed on antigen-presenting cells including DCs as wells as activated T cells and B cells. 14 We focussed on DCs in the ilea and blood of patients, as previous studies have shown that aggregated PD-L2 on DCs is essential for Th1 immunity 15 which drives CD pathology. 14 We focussed on DCs in the ilea and blood of patients, as previous studies have shown that aggregated PD-L2 on DCs is essential for Th1 immunity 15 which drives CD pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 PD-L2 is generally expressed on antigen-presenting cells including DCs as wells as activated T cells and B cells. 14 We focussed on DCs in the ilea and blood of patients, as previous studies have shown that aggregated PD-L2 on DCs is essential for Th1 immunity 15 which drives CD pathology. 14 We focussed on DCs in the ilea and blood of patients, as previous studies have shown that aggregated PD-L2 on DCs is essential for Th1 immunity 15 which drives CD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] A previous study examined PD-L1 and PD-L2 expression on CD90 + stromal cells in human colonic mucosa tissue and found lower expression of PD-L1 but not PD-L2. 14 We focussed on DCs in the ilea and blood of patients, as previous studies have shown that aggregated PD-L2 on DCs is essential for Th1 immunity 15 which drives CD pathology. While we found no differences in PD-L2 levels in the ilea from CD patients with controls, flow cytometry studies of blood DCs showed increased levels of PD-L2 while microscopy confirmed the protein is aggregated.…”
Section: Longitudinal Study Of Intestinal T Lymphocyte Subsets Duringmentioning
confidence: 99%
“…20,37 Similarly, PD-L1 was shown to be decreased in the inflamed mucosa of Crohn's disease patients with increased IFNγ levels. 38 Induced colitis experiments in mice showed that IFNγ is one of the most highly induced mediators in the inflamed gut. 39 This indicates that IFNγ is part of the tumor-induced inflammatory response and fits the idea that cancer is a chronic stimulus for the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study demonstrated that the colonic CD90 + stromal cells from Crohn's disease patients presented significantly lower PD‐L1, together with reduced capacity to suppress Th1 inflammation . Reduction of the PD‐1/PD‐L1 signaling thus appears to be a common mechanism through which the inflammation in Crohn's disease persists over time.…”
Section: Discussionmentioning
confidence: 99%
“…that T-bet, as the Th1-associated transcription factor, displayed significantly higher expression in more severe Crohn's disease patients, Interestingly, a recent study demonstrated that the colonic CD90 + stromal cells from Crohn's disease patients presented significantly lower PD-L1, together with reduced capacity to suppress Th1 inflammation. 26 Reduction of the PD-1/PD-L1 signaling thus appears to be a common mechanism through which the inflammation in Crohn's disease persists over time. A special type of Th17 cells with Th1 signature and expressing both IL-17…”
Section: Bacterial Stimulation Significantly Elevated Tbet Expressimentioning
confidence: 99%